Княжна Джаваха: повесть / Лидия Чарская - Чарская Лидия Алексеевна (Классика для школьников, 2017)
Экземпляры: ф.12 (20180725) / Инвентарный номер: 58533 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ч-22 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44